Déficit sensorial após AVC: prevalência e contribuição para a incapacidade funcional - Valdisson Sebastião Bastos (2023)
Introduction: Stroke results in important disabilities, such as sensory impairment, triggering functional changes and negative impacts on the health system. Sensory deficit after stroke has been described in the literature, but its prevalence has been little investigated, as well as the association with functional disability of those individuals. Objectives: To identify the presence of sensory impairment in adult stroke individuals, in the acute phase of the lesion, in an inpatient environment, in the city of Belo Horizonte. The secondary objective was to verify the contribution of proprioceptive and exteroceptive sensory impairments to their functional disability. Methods: This was an exploratory cross-sectional study with adult individuals in the acute phase of stroke, admitted to a public hospital. Clinical and demographic data were collected to characterize the sample. The Modified Rankin Scale was used to obtain functional disability data. Sensory impairment was identified by scoring the sensation subscale of the Fugl-Meyer Scale, and data from exteroception and proprioception were used for analysis. Step-wise multiple linear regression analysis was used to assess the contribution of proprioceptive and exteroceptive sensory impairments to the functional disability of these individuals. Results: A total of 2566 adult individuals diagnosed with stroke were recruited, with a mean age of 65 years, mostly suffering from ischemic stroke (86%) and a mean hospital stay of 13 days. The analysis showed a high prevalence of sensory impairment (57%), with exteroception impairment (48%) more prevalent than proprioception impairment (42%). There was an association between the variables, where the sensory impairment was able to explain 14% of the variance for functional disability. Alone, proprioceptive impairment explained 13% of the variance in Modified Rankin Scale scores. Exteroception impairment added 1% explanatory power to the model. Conclusion: Sensory impairment was identified in most of the sample, with significant prevalence and associated functional impact. Knowing the prevalence of sensory impairment, as well as better Investigating its contribution to functional losses, can contribute to a more efficient rehabilitation process.